Increased cranio-caudal spinal cord oscillations are the cardinal pathophysiological change in degenerative cervical myelopathy - Pfender, Nikolai; Rosner, Jan; Zipser, Carl M.; Friedl, Susanne; Schubert, Martin; Sutter, Reto; Klarhoefer, Markus; Spirig, José M.; Betz, Michael; Freund, Patrick; Farshad, Mazda; Curt, Armin; et al. (Frontiers in Neurology, 2023)
Introduction: Degenerative cervical myelopathy (DCM) is the most common cause of non-traumatic incomplete spinal cord injury, but its pathophysiology is poorly understood. As spinal cord compression observed in standard MRI often fails to explain a patient’s status, new diagnostic techniques to assess DCM are one of the research priorities. Minor cardiac-related cranio-caudal oscillations of the cervical spinal cord are observed by phase-contrast MRI (PC-MRI) in healthy controls (HC) while they become pathologically increased in patients suffering from degenerative cervical myelopathy. Whether transversal oscillations (i.e., anterior-posterior and right-left) also change in DCM patients is not known. Methods: We assessed spinal cord motion simultaneously in all three spatial directions (i.e., cranio-caudal; anterior-posterior; right-left) using sagittal PC-MRI and compared physiological oscillations in 18 HC to pathological changes in 72 DCM patients with spinal canal stenosis. Parameter of interest was the amplitude of the velocity signal (i.e., maximum positive to maximum negative peak) during the cardiac cycle. Results: Patients suffered from mild DCM (mJOA score 16 (14-18) points) and the majority (68.1 %) presented with multisegmental stenosis. The spinal canal was considerably constricted in DCM patients in all segments compared to HC. Under physiological conditions in HC, the cervical spinal cord oscillates in the cranio-caudal and anterior-posterior direction, while right-left motion was marginal (e.g., segment C5 amplitudes: cranio-caudal: 0.40 [0.27-0.48] cm/s; anterior-posterior: 0.18 [0.16-0.29] cm/s; right-left: 0.10 [0.08-0.13] cm/s). Compared to HC, DCM patients presented with considerably increased cranio-caudal oscillations as the cardinal pathophysiologic change in non-stenotic (e.g., segment C5 amplitudes: 0.79 [0.49-1.32] cm/s) and stenotic segments (e.g., segment C5 amplitudes: 0.99 [0.69-1.42] cm/s). In contrast, right-left (e.g., segment C5 amplitudes: non-stenotic segment: 0.20 [0.13-0.32] cm/s; stenotic segment: 0.11 [0.09-0.18] cm/s) and anterior-posterior oscillations (e.g., segment C5 amplitudes: non-stenotic segment: 0.26 [0.15-0.45] cm/s; stenotic segment: 0.11 [0.09-0.18] cm/s) remained on low magnitudes comparable to HC. Conclusion: Increased cranio-caudal oscillations of the cervical cord are the cardinal pathophysiologic change and can be quantified by PC-MRI in DCM patients. This study speaks to spinal cord oscillations as a relevant biomarker reflecting dynamic mechanical cord stress in DCM patients, potentially contributing to a loss of function.